Turkey - Country Economic Memorandum (CEM) : Sustaining High Growth - The Role of Domestic savings : Synthesis Report - World Bank (Washington, DC, 2013)
Domestic savings in Turkey declined significantly in the 2000s. The domestic savings rate declined from an average of 23.5 percent of gross national income in the 1990s to an average of 17 percent over the 2000-2008 period, and further to 12.7 percent in 2010. This decline was driven by the sharp fall in private saving, while public saving increased through most of the period. A strong fiscal adjustment underpinned the improvement in public savings in the post-2001 period. The adjustment was pursued to correct the fiscal expansion of the previous decade, and it led to a sharp reduction in the public debt to gross domestic product (GDP) ratio. This improved the public saving-investment balance and helped reduce the vulnerability of the economy to external shocks. With an expected increase in future investment needs, continued fiscal discipline will be vital for sustainable growth. The fall in private savings after 2001 was mostly a result of the decline in macroeconomic vulnerabilities. While the economy was growing fast, the positive impact of income growth on savings was overridden by an acceleration of private consumption stimulated by the increased availability of credit, fall in interest rates and previously postponed consumption. As the economy normalized and interest rates and inflation declined, so did household precautionary motives for saving. Eventually, however, continued economic stability and implementation of reforms discussed below should encourage saving by raising incomes. Structurally, Turkish households have a strong precautionary motive for savings. Macroeconomic vulnerabilities and the resulting unstable income streams, the risk of unemployment, and health risks are obvious reasons for household decisions to save. Declining interest rates (as in the 2000s) that reflected reduced risk premium and hence vulnerability reduced precautionary savings motives. Households where the head is an employer or self-employed rather than a wage earner tend to save more, while households where there is a green card holder (a non-contributory health program) save less, controlling for the income effect.